FROM DIGITAL GAMES TO COMPUTATIONAL THINKING: A META-ANALYTIC REVIEW IN MATHEMATICS EDUCATION - Suparman, Suparman; Juandi, Dadang; Turmudi, Turmudi (Sanata Dharma University Yogyakarta, 2025)
In the last ten years, there has been considerable growth in empirical studies examining the effects of digital games on mathematics learning and computational thinking (CT). However, a review of the existing literature indicates that the outcomes of digital game-enhanced math instruction on students' CT skills have yielded inconsistent results. This research intends to evaluate how effective digital game-supported mathematics education is in developing students' CT abilities, while taking into account various factors such as educational level, duration of the intervention, learning context, game developer, and type of game. A meta-analytic review was conducted, analyzing 15 pertinent studies published between 2011 and 2023, which produced 21 effect sizes and included a total of 8,911 students. Statistical analyses, including the Q Cochrane test, publication bias assessment, Z test, and sensitivity analyses, were performed using CMA software to scrutinize the data. The results indicated a statistically significant but modest positive effect (g = 0.344; p < 0.05) of digital game-supported math education on students' CT skills. Several factors, including the length of the intervention, the software developer, and the type of game, significantly impacted CT outcomes, whereas other factors, such as educational level and learning environment, did not show a significant influence. These findings suggest that digital game-supported mathematics instruction can be an effective technological approach to enhance students' computational thinking abilities.